2013
DOI: 10.1111/1574-6941.12125
|View full text |Cite
|
Sign up to set email alerts
|

Co-cultivation ofSorangium cellulosumstrains affects cellular growth and biosynthesis of secondary metabolite epothilones

Abstract: Sorangium cellulosum, a cellulolytic myxobacterium, is capable of producing a variety of bioactive secondary metabolites. Epothilones are anti-eukaryotic secondary metabolites produced by some S. cellulosum strains. In this study, we analyzed interactions between 12 strains of S. cellulosum consisting of epothilone-producers and non-epothilone producers isolated from two distinct soil habitats. Co-cultivation on filter papers showed that different Sorangium strains inhibited one another's growth, whereas epoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Among the three employed M. xanthus hosts, the yield ranges were similar in the DZ2 and DK1622 mutants, but much low in the SW504 mutants. The production abilities of epothilones in M. xanthus transposition recombinants from DZ2 or DK1622 were rather similar to that in those wild type epothilone-producing S. cellulosum strains [ 24 ]. However, in contrast to the 2:1 ratio of epothilones A to B or almost single A without B in S. cellulosum strains [ 24 ], the ratios of epothilones A–B produced in these M. xanthus producers were all approximately 1:5 (Additional file 2 : Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the three employed M. xanthus hosts, the yield ranges were similar in the DZ2 and DK1622 mutants, but much low in the SW504 mutants. The production abilities of epothilones in M. xanthus transposition recombinants from DZ2 or DK1622 were rather similar to that in those wild type epothilone-producing S. cellulosum strains [ 24 ]. However, in contrast to the 2:1 ratio of epothilones A to B or almost single A without B in S. cellulosum strains [ 24 ], the ratios of epothilones A–B produced in these M. xanthus producers were all approximately 1:5 (Additional file 2 : Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The production abilities of epothilones in M. xanthus transposition recombinants from DZ2 or DK1622 were rather similar to that in those wild type epothilone-producing S. cellulosum strains [ 24 ]. However, in contrast to the 2:1 ratio of epothilones A to B or almost single A without B in S. cellulosum strains [ 24 ], the ratios of epothilones A–B produced in these M. xanthus producers were all approximately 1:5 (Additional file 2 : Table S1). Compared to those previously reported epothilone-producing M. xanthus recombinants (approximately 0.1 mg/L or less) [ 10 , 11 ], some of the transposition transformants gave much higher productions under unimproved fermentation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the above advantages of epothilones as MSAs, they are microbial secondary metabolites with simple structures, which makes the fermentation and chemical synthesis be the major routes for getting more epothilones products since the discovery and the biological activity was confirmed. In 2013, Li et al [48] investigated the impact on the strains growth and epothilones production induced by different Sorangium cellulosum strains co-cultivation, and found that in co-cultivation can increase the epothilone production significantly than the pure cultures. While, it didn't clarify that the impacted factors of epothilones biosynthetic regulatory genes.…”
Section: Scheme 3 the Semi-synthesis Of Taccalonolidesmentioning
confidence: 99%
“…Epothilones are potential anticancer agents by their greater water solubility and efficacy against paclitaxel-resistant tumors [13, 14]. Researchers tried many methods to improve the epothilones yield, including co-cultivation of different strains [15], mutation and high-throughput screening of high-producing strains [16], immobilization of strains [17], heterologous expressions [1824] and manipulation of related genes [25, 26]. However, the yield is still limited.…”
Section: Introductionmentioning
confidence: 99%